Sequence-dependent energetics of the B-Z transition in supercoiled DNA containing nonalternating purine-pyrimidine sequences. - Ellison, M J (1985)
The likelihood that a given DNA sequence will adopt the Z conformation in negatively supercoiled DNA depends on the energy difference between the B form and the Z form for that sequence relative to other sequences in the same molecule. This energy can be viewed simply as a sum of energies for the nearest-neighbor interactions within the sequence plus the energy required to stabilize the B-Z boundaries. Knowledge of these energetic terms would be of value in predicting when sequences become left-handed in response to negative superhelicity. Here we present an approach that can be used to determine the free-energy changes associated with all the nearest-neighbor interactions that can occur in Z-DNA. Synthetic stretches of d(C-G)n containing one or two transversions were cloned into plasmids, and the extent of the B-Z transition as a function of negative superhelicity was determined for each insert by two-dimensional agarose gel electrophoresis. By subjecting the data to statistical mechanical analysis, it was possible to evaluate the energetic penalty resulting from each base-pair (bp) substitution. Guanine to cytosine transversions cost 2.4 kcal (1 cal = 4.18 J)/(mol X bp), whereas guanine to thymine transversions cost 3.4 kcal/(mol X bp), to stabilize in the Z conformation. We have used these numbers, along with energetic values determined by others for the B-Z transition, to predict that certain strictly nonalternating purine and pyrimidine sequences may adopt the Z form readily.